Written mathematical communication and self-confidence: A study of pre-service mathematics teachers - Reni Albertin Putri; Erwinda Viantasari; Wasilatul Murtafiah; Joel l. Alvarez (Program Studi Pendidikan Matematika, Universitas Nusantara PGRI Kediri, 2025)
Written mathematical communication is an essential competency for pre-service mathematics teachers, yet limited studies have explored this skill among them. Prior studies have highlighted a correlation between communication skills and an individual's level of self-confidence. Because of that, this study aims to describe the written mathematical communication abilities and self-confidence levels of mathematics teacher candidates. The research involved 20 sixth-semester students of the Mathematics Education Program at Universitas Negeri Malang, with six participants selected through purposive sampling. Using a descriptive qualitative approach, the study was conducted in three phases: planning, implementation, and conclusion. Data were collected through a written mathematical communication test and a self-confidence questionnaire, and analyzed using triangulation to ensure reliability. The results showed that two students with high self-confidence achieved level 4 in written mathematical communication, three students with moderate self-confidence attained levels 2–3, and one student with low self-confidence reached level 1. These findings indicate that self-confidence plays an important role in students’ written mathematical communication skills. Therefore, teacher education programs are encouraged to design learning activities that foster students’ confidence in expressing mathematical ideas in written form. Further studies with larger samples and broader contexts are recommended to validate these findings.